PENGARUH DUKUNGAN KELUARGA TERHADAP PENCEGAHAN DEPRESI PADA LANSIA WILAYAH DESA CAMPUREJO KECAMATAN MOJOROTO KEDIRI - Hostania, Chandra Isabella; Hidayah, Nur; Dewi, Ayuning Fitria (Jurnal AKP, 2010)
Depression is mood disorder, addressed by loss of interest and happiness in common activities.Many old person experience depression due to decrease of health status, pension, physical weakness,loss of partner or others. Family support can prevent the experience of depression. The objective of thisresearh is to explore the correlation between family supportand the experience of depression in oldperson.Research method was cross sectional by qualitative data. Respondents was family which hadold person as their member at Campurejo Village, Mojoroto Kediri. Data analyzed by Chi-Squareformula.The result of cross tabulation was: 38,46 % had gotten insufficient family support experiecedthe risk of depression, 41,03% had gotten moderate family support and did not experience depression,7,69 % had gotten great family support and had experienced the risk of depression, 12,82 % had gottengreat family support and did not experience depression. Chi-Square-statistical test showed thatHipothesis 0 (H0) was rejected and concluded that there was no relationship between family supportand the risk of depression on oldperson ( p-value >Î±or counted t < t-table ).Some old person who had had insufficient family support did not experience depression, due totheir activity in their environment, which been a social support for their physical and mental status. Itis suggested for familyto perform sufficient support the old person as their need and suggested to aldperson to actively perform their activities to prevent the experience of depression.